Generation of indicators of environmental and social liabilities for the subsystem of intelligence of statistics applied to activities hydrocarbon - Chamorro Armas, Sonia (2016)
This study allowed the generation of indicators of environmental and social liabilities which is measured the progress of the management of hydrocarbon activities and enhance the environmental remediation, through the application of instruments of public policy. Overexploitation of environmental services causes effects of predation or pollution to natural cycles, degrading the environment in which inhabit communities of flora, fauna and human, causing an infringement of their rights. We used a methodology descriptive and purposeful with a holistic approach which allowed to develop five indicators based on the power supply (number of spills, pools and ditches), pressure (number of claims by sources of pollution), State (satisfaction measures implemented by spills, pools and ditches) impact (number of conventions by hydrocarbon activity) and response (spills, pools and pits remediated by environmental authority number), at the beginning of the Integral service. Proposal that will allow contextualize the State of the management of the passive environmental in the Ecuador. The indicators proposed in the hydrocarbon (PRAS) to the affected sector by pollution, develop policies of exploitation of resources in a sustainable way.